Identifying key aspects to enhance predictive modeling for early identification of schistosomiasis hotspots to guide mass drug administration. - Yewen Chen; Fangzhi Luo; Leonardo Martinez; Susan Jiang; Ye Shen (PLoS Neglected Tropical Diseases)
Background Schistosomiasis, a neglected tropical parasitic disease, threatens the lives of over 250 million people worldwide. In schistosomiasis prevention, high-transmission areas that do not respond to treatments, known as hotspots, pose extreme challenges to the elimination of the disease. Accurate and early identification of such hotspots is crucial for timely intervention, but this is hindered by the limited availability of effective prediction methods. Methods Based on the Schistosomiasis Consortium for Operational Research and Evaluation (SCORE) project over a 5-year period, this study developed prediction methods for the first (baseline) year to identify hotspots. Three key aspects were considered: (i) collecting secondary data from public sources to complement baseline schistosomiasis infection data and constructing spatially weighted predictors to incorporate neighboring information; (ii) categorizing predictors to mitigate overfitting and quantifying the importance of each category in hotspot predictions; and (iii) investigating the hotspot imbalance distribution and addressing the imbalance with a sampling-based technique to improve prediction performance. Results Compared to the approach using only baseline infection data, the spatially weighted data fusion method achieved relative improvements (RIs) in hotspot prediction accuracy by fusing baseline infection data with each predictor category: 10% with biology, 8.6% with geography, 6.6% with society, 3.5% with baseline infection data around villages, 3.3% with environment, 1.8% with agriculture, and 7.2% with all predictors. Furthermore, across the same predictor combinations, applying the sampling-based technique with the proposed method yielded RIs of 6.5%-37.9%, compared to the approach that did not address the imbalance. Conclusion Spatially weighted data fusion using secondary data improved the early identification of schistosomiasis hotspots. Addressing the imbalance of hotspots can further improve the early identification of the hotspots.